The ‘’Four Too’’ in The Malinke of Odienne (North West of Cote d’Ivoire) Procreative Behaviours - Kouadio M’bra Kouakou Dieu-donne (European Scientific Journal, ESJ, 2016)
This paper aims at understanding the reasons for the existence of the “four too’’ as the level of motherhood risk in the Health District of Odienné. In that respect, quantitative tools (questionnaire, review of records) as well as qualitative tools (semi-structured interview, focus groups, literature and desk research) were resorted to. This range of methodological tool has enabled to underscore that the “too young”, “too old”, “too large” and “too close” motherhood, is a dominant practice in Odienné. This fact exposing women and girls to various health risks, is motivated by some socio-cultural logics. These socio-cultural beliefs about Motherhood, are out of step with the health recommendations.